MBCL-39. MEDULLOBLASTOMA IN PATIENTS WITH GORLIN SYNDROME: RESULTS FROM THE HIT STUDY GROUP. Issue 2 (22nd June 2018) - Meissner, Barbara; Mynarek, Martin; Ole Juhnke, B; von Hoff, Katja; Pietsch, Torsten; Kortmann, Rolf D; Warmuth-Metz, Monika; Bison, Brigitte; Rutkowski, Stefan
Abstract: Gorlin syndrome is an autosomal dominant inherited cancer predisposition syndrome characterized by basal cell carcinomas, odontogenic keratocysts, skeletal and multiple other anomalies, and medulloblastoma (MB). Most patients harbor a heterozygous germline mutation in PTCH1 or SUFU, genes that play a pivotal role in sonic hedgehog (SHH) signaling. We describe 17 patients with Gorlin syndrome diagnosed with MB between 1992 and 2017 who were treated according to HIT studies (HIT'91, SKK'92, HIT2000, and I-HIT-MED registry) and had available data on initial staging and treatment. Diagnosis of Gorlin syndrome was made clinically by fulfilling the syndrome criteria (N=9) or by proven PTCH1 (N=7) or SUFU (N=3) germline mutation. Median age at diagnosis of MB was 0.96 years. MB with extensive nodularity (N=5) and desmoplastic medulloblastoma (N=11) were the predominant histologic diagnoses, both typically associated with sonic hedgehog pathway activation (classical MB N=1). 12 of 17 patients had localized disease, 5 patients had metastases at initial diagnosis. 16 patients received HIT-SKK chemotherapy alone, 1 had primary craniospinal radiotherapy. HIT-SKK therapy was reduced in 3 patients with increased toxicities. Median follow up was 10.3 years. All patients are alive, two suffered from relapse 1.5 and 1.7 years after initial diagnosis. 10 year progression free survival was 82%±12%. Basal cell carcinoma was diagnosed in 2 patients, who were treated with radiotherapy. Gorlin syndrome and genetic counselling should be considered in all young children with SHH activated MB. Radiotherapy can be successfully avoided in most patients by HIT-SKK chemotherapy and is contraindicated within first-line therapy strategies.